Upaya Pengembangan Minat Literasi dan Kemampuan Menghafal Pada Anak Melalui Video Animasi di Teras Baca Sumberpasir Kabupaten Malang - Riris Dwi Puji Rahayu; Lala Mawarni Sutrisna; Ahmad Ahmad (Lifelong Education Journal, 2022)
Literacy interest and ability to memorize children is a potential that is needed and explored more effectively. The effort that needs to be made is to be able to collaborate on situations and conditions during the 4.0 revolution. For example, in Sumberpasir Village, Pakis District, Malang Regency, which has a Reading Terrace as an additional facility for the children of Sumberpasir Village. The Sumberpasir reading terrace has a tutoring program with 30 elementary school-age students. The main problem is that literacy interest in children is still not enough, so it becomes an obstacle to their memorization ability. The method used in this research is descriptive qualitative research through a case study approach. Related to the above problems, the solution offered by the author is an animation-based learning video that can help efforts to develop literacy interests and memorization skills for children under tutoring at the sand source reading terrace. The results obtained are (1) the implications of using animated video media as a strategy for developing literacy interests and memorization skills in children; (2) the role of animation in learning; and (3) the level of effectiveness of using animated videos to develop literacy interest and memorization skills in the children of the Sumberpasir Village. This animated video has some content that supports efforts to increase literacy interest and children's memorization skills at the Sumberpasir Reading Terrace. Keywords: Literacy, Memorizing, Video Animation